To veg or not to veg? The impact of framing on vegetarian food choice. (February 2020) - Krpan, Dario; Houtsma, Nanne
Abstract: Research suggests that consuming vegetarian foods is one of the key lifestyle changes that could reduce greenhouse gas emissions. However, transforming dietary habits to counter climate change has received little attention to date compared to other green behaviors. In three large pre-registered online studies conducted on 11, 066 US participants, the present research tested whether reframing the name of the vegetarian food category impacts the choice of dishes from this category in the context of restaurant menus. We showed that a pro-environmental frame (i.e. "Environmentally Friendly Main Courses for a Happy Planet"), a social frame (i.e. "Refreshing Main Courses for Relaxing Conversations"), and a neutral frame (i.e. vegetarian and non-vegetarian dishes mixed in the same section "Main Courses") all increased the likelihood of vegetarian choice compared to a vegetarian frame (i.e. "Vegetarian Main Courses"). Given that either of the three framing conditions (vs. the vegetarian frame) increased vegetarian food choice but no consistent differences emerged among them, the main message of the present research is that the absence of vegetarian framing, regardless of the alternative intervention, may make vegetarian choices more likely. In addition to testing the main effects of menus on vegetarian choice, we comprehensively examined the mechanism behind these effects by probing multiple mediators. Overall, our research offers new insights into how techniques stemming from psychology can enhance vegetarian food choice. Highlights: We tested how reframing the name of the vegetarian food category shapes food choices. Environmental, social, and neutral (vs. vegetarian) frames boosted vegetarian choice. No consistent differences emerged among the three non-vegetarian frames. We investigated the underlying psychological mechanisms behind the main effects.